The Effect of Thidiazuron and Naphtalene Acetic Acid on In Vitro Development of Eria hyacinthoides (Blume) Lindl Orchid - Rita Foorantika; Khoirun Nisa Pratiwi; Endang Semiarti (Journal of Tropical Biodiversity and Biotechnology, 2025)
Eria hyacinthoides (Blume) Lindl. is an Indonesian orchid species found in Sumatra, Java, and Bali. This orchid is a sympodial orchid with flowers that has fragrant aroma, suspected containing phytochemicals for herbal medicines, so mass plant propagation is necessary. The aim of this research is to obtain the best in vitro conditions for this orchid through somatic embryos using growth regulators and analysing the structure of the Dendrobium Orchid Homeobox 1 (DOH1) homologous gene in E. hyacinthoides to Dendrobium ‘Madame Thong-In’ which is known to induce bud formation. The method used in this study: (1) the leaves of the plant spread about 20 - 30 days from shoots measuring about 6.3-6.7cm on the mother plant aged ± 8 years, stored in an incubation room with picture of 16 hours of light and 8 hours of darkness in the heat. 25 ± 1 ℃, (2) compared Murashige and Skoog, Vacin and Went, Knudson C and New Phalaenopsis growth to get the best medium, (3) added PGR to medium (Thidiazuron (TDZ) 1 - 3 mg L-1 and Naphthalene-1-acetic acid (NAA) 1-3 mg L-1), (4) isolate   partial gen DOH1 homologous by using primer of DOH1, (5) analyse sequence of PCR products. Optimal medium for callus embryogenesis production from leave was Knudson C + TDZ 1 mg L-1 + NAA 1 mg L-1. Amplification of DNA fragments using degenerate primers of DOH1 resulted 175 bp, indicating similarity about 88.64 % with between the DOH1 gene structure in E. hyacinthoides and in Dendrobium ‘Madame Thong-In’.